The Role of Interest Rate Policy in Controlling Indonesian Government Debt - Salma Aparatunisa; Yulianah Yulianah; Satrio Sulistiyanto; Agustina Septiana; Marintan Anastasya Putri (Advances: Jurnal Ekonomi & Bisnis, 2026)
Purpose: This study analyzes the role of the benchmark interest rate policy implemented by Bank Indonesia in controlling Indonesia’s government debt burden through monetary and fiscal policy coordination. Research Method: This study uses a qualitative descriptive approach based on secondary data from Bank Indonesia reports, Ministry of Finance of the Republic of Indonesia publications, DJPPR reports, state budget documents, and macroeconomic policy reports during the 2020–2025 period. Data were analyzed through document review, descriptive interpretation, and source triangulation. Results and Discussion: The findings indicate that benchmark interest rate policy influences debt-servicing costs, sovereign bond yields, exchange-rate stability, SBN auction effectiveness, and investor confidence. Global monetary tightening and exchange rate volatility also affect refinancing conditions and government debt management strategies. Implications: The findings emphasize the importance of monetary-fiscal coordination in maintaining fiscal sustainability and financial market stability. Originality: This study integrates benchmark interest rate dynamics, sovereign financing conditions, and fiscal sustainability within Indonesia’s post-pandemic economic context.